(3GdCfSGHs - (3GdSeYGfj , YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj GdTGaYj GdMGaX, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM CHhGHefM GSHGH GdehGgH CNHQfG GHh eMeO jMji hCHh GdMSf eMeO s
(3BNQgG (B:s
(3hKeGQ hGTLGQ hHgG ef GdYQH Jeje hcGf OYjd GHf Ydi GdTGYQ hdgG ddYHGS Hf LYaQ heMeO Hf GdGTYK ddPFH s
(3GfXQ GjVkG Qbe (B68 (3JGQjNs
(3dg adef dcHQ MLeIs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs